2019
DOI: 10.1038/s41598-019-52291-6
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Arginine Methyltransferases 1 and 5 affect Myc properties in glioblastoma stem cells

Abstract: Protein Arginine (R) methylation is the most common post-translational methylation in mammalian cells. Protein Arginine Methyltransferases (PRMT) 1 and 5 dimethylate their substrates on R residues, asymmetrically and symmetrically, respectively. They are ubiquitously expressed and play fundamental roles in tumour malignancies, including glioblastoma multiforme (GBM) which presents largely deregulated Myc activity. Previously, we demonstrated that PRMT5 associates with Myc in GBM cells, modulating, at least in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…The mechanistic interplay between aDMA and sDMA of MYCN is currently unclear, but it appears that a certain threshold of arginine methylation regardless of whether it is aDMA or sDMA is required for cell survival, as demonstrated by induction of cell apoptosis in cells depleted of either PRMT1 or PRMT5 through RNA interference 3,4 . This idea is supported by a recent report showing that MYC is both asymmetrically and symmetrically dimethylated by PRMT1 and PRMT5, respectively, with different functional properties in glioblastoma 30 . Second, the high potency of decamidine we observed in our current study may be due to combined PRMT1 and PRMT5 inhibition.…”
Section: Discussionsupporting
confidence: 59%
“…The mechanistic interplay between aDMA and sDMA of MYCN is currently unclear, but it appears that a certain threshold of arginine methylation regardless of whether it is aDMA or sDMA is required for cell survival, as demonstrated by induction of cell apoptosis in cells depleted of either PRMT1 or PRMT5 through RNA interference 3,4 . This idea is supported by a recent report showing that MYC is both asymmetrically and symmetrically dimethylated by PRMT1 and PRMT5, respectively, with different functional properties in glioblastoma 30 . Second, the high potency of decamidine we observed in our current study may be due to combined PRMT1 and PRMT5 inhibition.…”
Section: Discussionsupporting
confidence: 59%
“…Our study results showed that PRMT1 downregulation was correlated with PD-L1 downregulation in PDAC tumors. Studies suggest that PRMT1 regulates c-myc gene expression and function[ 32 , 33 ]. Current data show that c-myc , an important signaling hub and driver gene, is commonly overexpressed and aberrantly activated in PDAC[ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a promising target is PRMT5, a type II methyltransferase that is responsible for depositing the majority of the symmetrical dimethylation marks on arginines (SDMA) and methylates several RNA binding proteins and spliceosomal proteins [133][134][135]. In MYC-driven tumors, PRMT5 enhances assembly of spliceosome components and MYC expression [136,137]. Since MYC promotes GBM cell survival, proliferation, invasiveness, and self-renewal, its expression is inversely correlated with patient survival [53,[138][139][140].…”
Section: Therapeutic Approachesmentioning
confidence: 99%